Enhanced In-Situ Bioremediation of Petroleum-Contaminated Soil: A Review - Rizka Amelia Situmorang; Qomarudin Helmy (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
Petroleum is still one of the main sources of energy even though many energy sources have been discovered today. The growing petroleum industry is directly proportional to the contamination that can be caused by this industry. Bioremediation is an environmentally friendly and cost-effective technology that has recently become a favorite technology in dealing with petroleum contaminated soil waste. This technology can be carried out directly in the polluted area, to minimize dredging and transportation costs. However, natural attenuation has limited potential and needs a longer time to degrade hydrocarbon. The article aims to outline the application and factors to consider in in-situ bioremediation of petroleum-contaminated soil.